(untitled) (Perner’s Contacts, 2011)
This paper deals with the problematic design of a railway networks models within the frame of regional railway lines in the Czech Republic. The utilization of satellite navigation for rolling stock positioning is discussed. The analysis of data is performed for the needs of design a graph representation within a selected segment of the rail network. Consequently the design of a railway infrastructure models with two levels of detail. For the testing of design railway network is built software tool. This software tool is able to visualize of rolling stock movements by simulation. The data items (time-stamped) of rolling stock movements are from real history. In addition, generated data reflecting potential collision train movements (typically within the frame of single-track line section) are exploited.